Accessibility and Effectiveness in Newborn Referral System in Lucknow - Bhaskar, Spriha; Kumar, Anil (Journal of Neonatal Surgery, 2025)
The current study's goals were to evaluate how the newborn referral system contributes to reduce infant morbidity and death by guaranteeing prompt and adequate medical treatment. The study employed a mixed-method approach, combining qualitative information from caregivers and medical professionals with quantitative data from hospital records. The study was carried out in the Government and private hospitals situated in Uttar Pradesh. Over the course of a year, this prospective observational research was carried out. There were 1000 referred babies that were recruited in the research overall. The findings indicated that low birth weight (30%), infections and sepsis (20%), jaundice (10%), respiratory distress (35%) and birth traumas (5%), accounted for the bulk of infant referrals. The results show that although there are referral systems in place, their effectiveness is severely hampered by deficiencies in communication, infrastructure and transportation. In order to improve the results of infant referrals, this study suggests legislative changes and infrastructure improvements. The study's findings will be useful in evaluating its advantages, disadvantages and possible areas for development.